Genomic clinical trials and predictive medicine - Simon, Richard M., 1943- (Practical guides to biostatistics and epidemiology., 2013)
This book focuses on novel approaches that provide a reliable basis for identifying what kinds of patients are likely to benefit from the each new treatment.